Efetividade dos direitos fundamentais nas relações de trabalho por meio do processo judicial eletrônico - Moraes, Camila Miranda de (2019)
This thesis has the purpose of analyzing, at the Democratic State, how technology provided by the system of the electronic judicial procedure can contribute to increase the defense of worker´s fundamental rights in brazilian Labour Law Courts. For that, we´ll study in the first chapter the meanings of the expression “access to justice” what fundamental rights are, their characteristics, classification and functions. We will analyse how the Constitution of 1988 deals with the problem of access to justice in Brazil. The second chapter will be devoted to jurisdiction as we know it nowadays: its characteristics, principles, goals, types and how the Judiciary system is organized in Brazil and how Labour Law Courts organize themselves. The third chapter will study the electronic judicial procedure in Labour Law Courts. We´ll start from the concept of technology, the birth of computers, the laws that preceeded computerization of judicial procedures in Brazil. We will analyse Law 11.419 of December 19 2006 which regulated computerization of judicial procedures in Brazil, and the laws that came after that and also played an important part. The last topic will be a comparative analysis of the electronic judicial procedure in other countries. The fourth chapter will study the theory of principles, the difference between principles and rules, to aim at the constitutional principles of process, the principles of labour law process and the principles of electronic judicial procedure. After that, on the fifth chapter, we will talk about the division of tasks between labour law judges and how the electronic judicial procedure has tools that can enhance the work methodology in ways of making room to fulfill the order contained in article 111 of the Constitution of 1988 and to improve the defense of the worker´s fundamental rights